[William Ogilvie correspondence]. - Ogilvie, William, 1736-1819; Electronic Enlightenment Project ([Oxford] : Electronic Enlightenment Project, 2008)
Electronic Enlightenment Scholarly Edition of Correspondence is an online, fully cross-searchable collection of correspondence from the 17th to 20th century. It combines never previously published materials with best scholarly editions, and is updated annually. Also included are extensive scholarly annotations and the Electronic Enlightenment Biographical Dictionary. The contributors and addressees include authors, philosophers, craftsmen ... The topics covered include education, religion, politics, art, science, the slave trade, gender issues .... Most of the correspondents are from France, Germany, Italy, the British Isles and North America, but there are also contributions from Spain, Portugal, Russia, ....
Mode of access: World Wide Web.
Description based on Electronic Enlightenment Scholarly Edition of Correspondence as at 20 April 2017; title supplied by cataloguer.
Keywords: Ogilvie, William, -- 1736-1819 -- Correspondence; Teachers -- Scotland -- Correspondence; Authors, Scottish -- Correspondence; Scholars -- Scotland -- Correspondence; Personal correspondence; Biographies; Business correspondence